Predictor Analysis in Radiofrequency Ablation of Benign Thyroid Nodules: A Single Center Experience - Bisceglia, Alessandro; Rossetto, Ruth; Garberoglio, Sara; Franzin, Angelica; Cerato, Alice; Maletta, Francesca; Papotti, Mauro Giulio; Ghigo, Ezio; Pagano, Loredana; Maccario, Mauro; Garberoglio, Roberto (Frontiers in Endocrinology, 2021)
Purpose To confirm the efficacy of ultrasound (US) guided radiofrequency ablation (RFA) in the treatment of benign thyroid nodules, we evaluated as primary outcome the technical efficacy and clinical success in a single center dataset. The secondary outcome was to find a correlation between nodules’ pre-treatment features and volume reduction rate (VRR) ≥75% at 12 months after RFA and during follow-up period. Methods This retrospective study included 119 consecutive patients (99 females, 20 males, 51.5 ± 14.4 years) with benign thyroid nodules treated in our hospital between October 2014 and December 2018 with a mean follow-up of 26.8 months (range 3–48). Clinical and US features before and after RFA were evaluated by a US examination at 1, 3, 6, 12 months and annually thereafter up to 48 months. Results The median pre-treatment volume was 22.4 ml; after RFA we observed a statistically significant volume reduction from the first month (11.7 ml) to the last follow-up (p < 0.001 for all follow-up times). The median VRR was 47.1, 55.3, 61.2, 67.6, 72.8, 71.3, and 62.9% at 1, 3, 6, 12, 24, 36, and 48 months of follow-up respectively, showing a progressive significant improvement up to 24 months (VRRs 1 vs 3 months, 3 vs 6 months and 6 vs 12 months p < 0.001, 12 vs 24 months p = 0.05) while no differences at 24 vs 36 and 36 vs 48 months were observed. Symptoms improved significantly (complete resolution 64.35%, partial resolution 35.65%), and neck circumference was reduced as compared to pre-treatment (p < 0.001). Lower pre-treatment neck circumference (37.5 vs 36.0 cm, p = 0.01) was a positive predictor of VRR ≥75% at 12 months. Macrocystic echostructure (HR 2.48, p 0.046) and pre-treatment volume >22.4 ml (HR 0.54, p 0.036) were found to be independent positive and negative predictors of VRR ≥75% respectively. One-month post RFA VRR ≥50% represented the best positive predictor of technical success. Conclusions This study confirmed the efficacy of RFA in the treatment of benign thyroid nodules. In particular we show that by selecting macrocystic nodules smaller than 22.4 ml better long-term response can be achieved, which is predicted by an early shrinkage of the nodule.